Incorporating Innovative Techniques Toward Extrapolation and Efficient Pediatric Drug Development. (September 2019) - Gamalo-Siebers, Margaret; Hampson, Lisa; Kordy, Kattayoun; Weber, Sebastian; Nelson, Robert M.; Portman, Ronald
The conduct of pediatric clinical trials is legally required, monitored, and encouraged in major geographic areas such as the United States and Europe. However, because pediatric patients are considered vulnerable populations, they should only be enrolled as research subjects in a clinical trial if enrolling adult subjects will not be able to answer the scientific question related to the health and welfare of children. Thus, there is an ethical obligation to build the foundation for the use of pediatric extrapolation and related innovative analytical strategies with appropriately designed pediatric and adult clinical trials to reduce the amount of, or general need for, additional information needed from children to reach conclusions. This manuscript discusses innovative applications of clinical trial designs, analytic strategies to more efficiently leverage prior information, and modeling approaches that impact the data required to determine efficacy of an investigational drug in pediatrics. The planning of pediatric trials and regulatory interactions related to required pediatric studies and the expectations for innovative analytics are also discussed.